Slovakia and its environmental transformation: measuring environmental attitudes using the new ecological paradigm - Marcineková, Lenka; Štěrbová, Martina; Výbošťok, Jozef; Hajdúchová, Iveta; Giertliová, Blanka; Šulek, Rastislav; Sarvašová, Zuzana; Šálka, Jaroslav (Frontiers in Psychology, 2024)
Many scientists have studied the relationship between society and the environment. The New Ecological Paradigm (NEP) has been repeatedly used for the analysis of public environmental attitudes, as the public pays increased attention to the environmental issues, sustainability, or the climate crisis. Our paper deals with the use of the NEP to study and identify public environmental attitudes in the Slovak Republic. We discovered a deviation of our results from the NEP, as we identified altered environmental attitudes, which we find acceptable, as environmental attitudes are a delicate set of values encompassing different, yet interrelated facets. According to our results, we were able to classify our respondents into those with technocentric, ecocentric, and resiliocentric attitudes, while up to 70% of respondents hold the ecocentric attitude. These findings could be influenced by the fact that no significant changes in the population’s lifestyle have been required up to now. The NEP has proven to be an important predictive tool in assessing public environmental attitudes to determine readiness for environmental transformation. Nevertheless, we recommend using a combination of analysis that includes evaluating the impact of demographic factors to achieve higher-quality results.